Socialization of Organic and Inorganic Waste and the Addition of Garbage Bins in Kampung. Curug Village. Wangun Jaya - Noviansyah, Darwin; Satrya Fajar Kusuma, Fitrah (Universitas Ibn Khaldun, 2023)
Curg Village is a village located in Wangun jaya Village, Lewisadeng District, Bogor Regency, West Java Province. Curug village is a village where the majority of the population's livelihood includes agriculture and farming, Awareness and Concern to handle waste from the village community seems to be still very lacking. The habit of throwing garbage into the nearest river is one of the mistakes of the community that results in the accumulation of garbage downstream of the river. It is feared that this will be emulated by future generations such as young people and children. These concerns can be reduced by growing public awareness of the importance of disposing of waste in its place and the selection of waste, the hope to be achieved from this program is that the community begins to understand the importance of managing waste and can distinguish between organic and inorganic waste, because it will not only preserve the environment but also can help residents understand that waste also has its selling value such as recycling waste that can be made bags and wallet. There is also the provision of trash cans at several points in Curug Village, the community can carry out real activities in waste management by selecting both organic and inorganic waste.